1992
DOI: 10.1001/archsurg.1992.01420040042006
|View full text |Cite
|
Sign up to set email alerts
|

Twelve Hundred Open Cholecystectomies Before the Laparoscopic Era

Abstract: Records of 1200 consecutive open cholecystectomies, performed by a teaching service of a large, urban hospital in the years immediately preceding the laparoscopic era, were reviewed for morbidity and mortality rates. The mortality rate in this series was 1.8%, chiefly in the older age groups. Only two ductal injuries were incurred. A review of published series from 1952 through 1990 revealed a mean mortality rate of 1.53%. These recent observations on the morbidity and mortality after open operation should pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
74
1
7

Year Published

1993
1993
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(84 citation statements)
references
References 12 publications
2
74
1
7
Order By: Relevance
“…This has important implications for community care of the elderly 6 . By contrast with one previous report 2,6 93% of the patients who responded to the survey were pleased with the end result of the procedureand despite the frequent persistence of abdominal symptoms. A similar frequency of overall improvement despite a high number of patients with persistent abdominal pain post cholecystectomy has been reported previously 4 .…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…This has important implications for community care of the elderly 6 . By contrast with one previous report 2,6 93% of the patients who responded to the survey were pleased with the end result of the procedureand despite the frequent persistence of abdominal symptoms. A similar frequency of overall improvement despite a high number of patients with persistent abdominal pain post cholecystectomy has been reported previously 4 .…”
Section: Discussioncontrasting
confidence: 88%
“…Loss of reservoir function of the gall bladder, which results in disturbance of bile metabolism and entero-hepatic cycling has been implicated as a cause. 1,2 .This study was designed to assess symptomprevalenceof patients with symptomatic gallstone disease during pre and postlaparoscopic cholecystectomy.…”
Section: Introductionmentioning
confidence: 99%
“…Biliary leakages are considered an early complication and biliary strictures are a late complication. It is observed that the rate of clinically-relevant bile leaks after conventional open cholecystectomy ranges was between 0.1% and 0.5% (1)(2)(3). Biliary leakages have increased after the development of laparoscopic cholecystectomy (LC) by up to 3% (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…Open CBDE has been shown in RCTs to result in morbidity ranging from 11 % to 14 % and mortality from 0.6 % to 1 % [5]. Interestingly, Morgenstern et al [29] reported on 220 open CBDE before the laparoscopic revolution. Their results revealed no mortality in patients under 60 years of age and 4.3 % mortality in those over 60.…”
Section: Stones Discovered Intraoperativelymentioning
confidence: 99%